Altered T-Lymphocyte Biology Following High-Dose Melphalan and Autologous Stem Cell Transplantation With Implications for Adoptive T-Cell Therapy - Mika, Thomas; Ladigan-Badura, Swetlana; Maghnouj, Abdelouahid; Mustafa, Bakr; Klein-Scory, Susanne; Baraniskin, Alexander; Döhring, Sascha; Fuchs, Ilka; Ehl, Stephan; Hahn, Stephan A.; Schroers, Roland (Frontiers in Oncology, 2020)
In relapsed and refractory (r/r) multiple myeloma (MM), adoptive cell therapies (ACT) including CAR-T-cells are under clinical investigation. However, relapse due to T-cell exhaustion or limited persistence is an obstacle. Before ACT are considered in MM, high-dose (HD) melphalan followed by autologous stem-cell transplantation (autoSCT) has been administered in most clinical situations. Yet, the impact of HD chemotherapy on T-cells in MM with respect to ACT is unclear. In this study, T-lymphocytes’ phenotypes, expansion properties, lentiviral transduction efficacy, and gene expression were examined with special respect to patients following HD melphalan. Significant impairment of T-cells’ expansion and transduction efficacy could be demonstrated. Expansion was diminished due to inherent disadvantages of the predominant T-cell phenotype but restored over time in principle. The quantitative fraction of CD27-/28- T-cells before expansion was predictive of T-cell yield. Following autoSCT, the transduction efficacy was reduced by disturbed lentiviral genome integration. Moreover, an unfavorable T-cell phenotype after expansion could be demonstrated. In an initial analysis of CD107 degranulation impaired T-cell cytotoxicity was detected in one patient following melphalan and autoSCT. The findings of our study have implications with respect to the time point of leukapheresis for e.g. CAR-T-cell manufacturing. Our results point to a preferred interval of more than 3 months until patients should undergo cell separation for CAR-T therapy in the specific situation post HD melphalan/autoSCT. Monitoring of CD27-/28- T-cells, has the potential to influence clinical decision making before apheresis in MM.